1983
DOI: 10.1111/j.1432-1033.1983.tb07756.x
|View full text |Cite
|
Sign up to set email alerts
|

The function of Nα‐acetylation of the eye‐lens crystallins

Abstract: The putative protective role of the Nu-acetyl group of proteins has been investigated. Synthetic, non-acetylated Nterminal tetrapeptides of the aA2-and 711-crystallin chains are good substrates for leucine aminopeptidase, while the acetylated ones are completely resistant. In the native, non-acetylated, y-crystallin the N terminus is not degraded by leucine aminopeptidase. Newly synthesized aA2-crystallin, in which the normally occurring N-terminal acetylation has been prevented during cell-free translation, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1984
1984
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…This strategy is simple, broadly applicable, and improves peptide biostability without altering the backbone and side chain functional groups necessary for full biological activity . Aminopeptidases are the major source of proteolytic activity in most tissues, and their action represents the predominant degradation pathway for peptides containing a free N-terminal amine, even in the presence of an unprotected carboxyl terminus. Protection of the N-terminus is therefore essential to peptide stability in vivo, and methods such as N-terminal acetylation and methylation have found widespread use. , Additionally, our laboratory has observed that N-terminal substitution with α-azido acids, methyl groups, or hydrogen atoms substantially increased peptide biostability, hydrophobicity, and activity in various peptide models without adversely affecting other pharmacokinetic properties. This suggests that incorporation of appropriate N-terminal modifications may have the potential to improve a greater range of peptide characteristics than currently recognized. However, direct comparisons between N-terminal modifications with respect to a variety of pharmacokinetic (PK a Abbreviations: NT, neurotensin; hNTR1, human neurotensin receptor 1; BBB, blood−brain barrier; Hlys, homolysine; ip, intraperitoneal; MALDI-TOF, matrix-assisted laser desorption ionization time-of-flight; MTBE, methyl- tert -butyl ether; Mtr, 4-methoxy-2,3,6-trimethylbenzenesulfonyl; NN, neuromedin N; NT, neurotensin; NTR, neurotensin receptor; Pbf, 2,2,4,6,7-pentamethylbenzofuran-5-sulfonyl; PK, pharmacokinetic; SAR, structure−activity relationship; X Ps , ( S )-(−)-4-(phenylmethyl)-2-oxazolidinone. ) parameters have not been reported, which is the subject of this report.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This strategy is simple, broadly applicable, and improves peptide biostability without altering the backbone and side chain functional groups necessary for full biological activity . Aminopeptidases are the major source of proteolytic activity in most tissues, and their action represents the predominant degradation pathway for peptides containing a free N-terminal amine, even in the presence of an unprotected carboxyl terminus. Protection of the N-terminus is therefore essential to peptide stability in vivo, and methods such as N-terminal acetylation and methylation have found widespread use. , Additionally, our laboratory has observed that N-terminal substitution with α-azido acids, methyl groups, or hydrogen atoms substantially increased peptide biostability, hydrophobicity, and activity in various peptide models without adversely affecting other pharmacokinetic properties. This suggests that incorporation of appropriate N-terminal modifications may have the potential to improve a greater range of peptide characteristics than currently recognized. However, direct comparisons between N-terminal modifications with respect to a variety of pharmacokinetic (PK a Abbreviations: NT, neurotensin; hNTR1, human neurotensin receptor 1; BBB, blood−brain barrier; Hlys, homolysine; ip, intraperitoneal; MALDI-TOF, matrix-assisted laser desorption ionization time-of-flight; MTBE, methyl- tert -butyl ether; Mtr, 4-methoxy-2,3,6-trimethylbenzenesulfonyl; NN, neuromedin N; NT, neurotensin; NTR, neurotensin receptor; Pbf, 2,2,4,6,7-pentamethylbenzofuran-5-sulfonyl; PK, pharmacokinetic; SAR, structure−activity relationship; X Ps , ( S )-(−)-4-(phenylmethyl)-2-oxazolidinone. ) parameters have not been reported, which is the subject of this report.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] Protection of the N-terminus is therefore essential to peptide stability in vivo, and methods such as N-terminal acetylation and methylation have found widespread use. 14,[16][17][18][19] Additionally, our laboratory has observed that N-terminal substitution with R-azido acids, methyl groups, or hydrogen atoms substantially increased peptide biostability, hydrophobicity, and activity in various peptide models without adversely affecting other pharmacokinetic properties. [20][21][22] This suggests that incorpora-tion of appropriate N-terminal modifications may have the potential to improve a greater range of peptide characteristics than currently recognized.…”
Section: Introductionmentioning
confidence: 99%
“…34) It has been reported that various metalloaminopeptidases efficiently catalyze the hydrolysis of non-acetylated proteins while N-terminalacetylated counterparts are poor substrates for these enzymes. 35,36) Based on these observations, we constructed the working hypothesis that the apparent decrease in the protein level of the non-acetylated " isoform under drought involves preferential decomposition of this isoform by metalloaminopeptidases. As a first step to test this hypothesis, we examined whether the non-acetylated " isoform is a good substrate for metalloaminopeptidases in vitro.…”
Section: Susceptibility Of the Non-acetylated " Isoform To Metalloamimentioning
confidence: 99%
“…However, there is only limited evidence bearing on this point and not all of it is compelling. For example, attempts to establish that proteins normally N"-acetylated are more unstable without this modification have been unconvincing (Brown, 1979;Driessen et al, 1983). Nonetheless, the ubiquitous distribution of these enzymes in eukaryotic cells and their highly conserved substrate specificity (Persson et al, 1985;Sherman et al, 1986) argue for a significant role; one such possible function, directing the early routes of protein turnover, is described below.…”
mentioning
confidence: 99%